Exploring the socio-ecological barriers & facilitators to reducing meat consumption in Gugulethu, Western Cape - Wolpe, Hannah (Department of Public Health and Family Medicine, 2026)
Meat consumption is on the rise in low- and middle-income countries such as South Africa, contributing towards myriad environmental and health repercussions, including the non-communicable disease crisis. However, most research on the topic originates from Western contexts and focuses on individual factors. This exploratory, socio ecological study is the first of its kind, aiming to aid in the development of public health interventions to combat the anticipated growth in demand for meat. Five qualitative focus groups held with residents of Gugulethu, Cape Town (n = 42) revealed that the vast accessibility and affordability of meat plays a significant role in dietary decisions, with several participants describing feelings of powerlessness over their consumption. Eating meat was furthermore described as a cultural imperative, with plant-based options typically considered untraditional, mundane, impractical, and often inaccessible. Meat's association with race, socioeconomic status, and gender all arose as topics of discussion. Participants identified the use of moderation, meat replacements (e.g., soy) and familiar recipes as strategies for curbing meat consumption. Reducing meat consumption requires a range of contextualised, interdisciplinary interventions: Government-led efforts are needed to make healthy choices easy choices, particularly for disadvantaged communities, by making such foods more accessible, convenient, and affordable in multiple settings (e.g., through subsidisation and incentives). Social marketing campaigns may be instrumental in shifting norms, with 'nudge' interventions providing cost-effective strategies to promote healthier choices. Lastly, individual interventions including awareness-creation and skills-development would help facilitate widespread change